Influence of the quality implementation of a physical education curriculum on the physical development and physical fitness of children - Starc Gregor; Strel Janko (BMC, 2012)
Abstract Background This study was constructed as a comparison group pre-test/post-test quasi-experiment to assess the effect of the implementation of the PE curriculum by specialist PE teachers on children's physical development and physical fitness. Methods 146 classes from 66 Slovenian primary schools were assigned to quasi-test (71) and quasi-control (75) groups. Data from the SLOFIT database was used to compare the differences in physical fitness and development between groups of children whose PE lessons were delivered by specialist PE teachers from the second grade onwards (quasi-test, n = 950) or by generalist teachers in all first three grades (quasi-control, n = 994). The Linear Mixed Model was used to test the influence of specialist PE teachers' teaching. Results The quasi-control group showed significantly lower improvement of physical fitness by -0.07 z-score units (95% CI -0.12 to 0.02) compared to the quasi-test group. A significant difference of -0.20 (-0.27 to -0.13) was observed in explosive strength, and of -0.15 (-0.23 to -0.08) in running speed, and in flexibility by -0.22 (-0.29 to -0.14). No significant differences in physical development were observed. Conclusions Specialist PE teachers were more successful than generalist teachers in achieving greater improvement of children's physical fitness, but no differences were observed in physical development of quasi-test and quasi-control group.